Menempa Masa Depan Inklusif: Peran Inspiratif Guru SLB Ayodya Tulada Mendobrak Segregasi Pinggiran Surabaya - Vanny Wulandari; Nova Estu Harsiwi (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to investigate the inspiring roles of teachers in SLB Ayodya Tulada in realizing inclusive education for children with special needs (ABK) amidst limitations in the suburbs of Surabaya. A qualitative research method was employed, utilizing in-depth interviews and observations to gather data. The findings revealed the pivotal role of teachers in designing inclusive learning, fostering social interaction among students, and breaking down stigma towards ABK. The study demonstrates that inclusive education can be achieved through strong commitment, competence, and collaboration.